Gender and left ventricular structural and functional differences in pulmonary hypertension among end stage renal disease patients on maintenance hemodialysis - Levin, Daniel B; Malik, Umar; Ajaaj, Ihab; Blaschke, Jon P; Skipper, Betty; McClelland, Sandra L; Fagan, Kathleen; Harford, Antonia M; Zager, Philip G; Raizada, Veena (Journal of Clinical Nephrology, 2019)
Introduction: Pulmonary hypertension (PH) is prevalent in hemodialysis (HD). In the general population, more women than men have PH due to left ventricular (LV) disease with preserved ejection fraction (EF). Little is known about the gender-specific prevalence of PH and associated LV abnormalities in patients with end stage renal disease (ESRD) on HD. Our aim was to evaluate gender differences and LV structural and functional changes in PH among ESRD patients on HD. Methods: Ninety-four patients (ages 23-77 years) underwent echocardiography after HD. Patients were divided based on estimated pulmonary artery systolic pressure (PASP) (Group A PASP < 40 mm Hg, Group B PASP ≥ 40 mm Hg). LV measurements included LV mass, LV internal dimensions, and LV ejection fraction (EF). LV diastolic function (LVDF) was assessed from mitral inflow deceleration time (DT) and E/A ratio. Results: Fifty-five patients (59%) had PH, including 32 of 49 men (65%) and 23 of 45 women (51%). LVEF was lower in Group B (46.4 ± 17.6 vs. 62.4 ± 14.4%, p < 0.001). Men with PH had higher LVIDd, cm (5.52 ± 0.89 vs 4.78 ± 0.75, p < 0.001), LVIDs, cm (3.75 ± 0.94 vs 3.14 ± 0.91, p = 0.03) LV mass, g (236 ± 74vs 189 ± 56, p = 0.02) and lower LVEF (40.0 ± 16.7 vs 52.0 ± 15.6, p = 0.008) than women. Conclusion: Patients on HD have a high prevalence of PH. PH was not associated with clear LV structural changes. There was a depression in LV systolic function without changes in LVDF. PH patients were more often men with hypertrophied LV with depressed LV systolic function.